2021
DOI: 10.1590/1983-40632021v5168175
|View full text |Cite
|
Sign up to set email alerts
|

Flowering induction in mango tree: updates, perspectives and options for organic agriculture

Abstract: The artificial flowering induction in mango tree is the most important crop management in mango orchards and requires greater attention from growers. The management involves three steps: stoppage of plant growth, branch maturation and flowering induction with nitrates. The first stage starts with the application of paclobutrazol to the soil. However, problems with the use of excessive concentrations are common and lead to the accumulation of residues in the soil. In addition, the use of paclobutrazol is not al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
(55 reference statements)
0
7
0
1
Order By: Relevance
“…In this study, amino acids levels increased significantly in the 30–100 days following SPD treatment, but not in the 80–100 days following water treatment ( Shivashankara, Geetha & Roy, 2019 ; Nj et al., 2017 ). The results showed these pathways respond to floral induction of mango ( Prates et al, 2021 ).…”
Section: Discussionmentioning
confidence: 95%
“…In this study, amino acids levels increased significantly in the 30–100 days following SPD treatment, but not in the 80–100 days following water treatment ( Shivashankara, Geetha & Roy, 2019 ; Nj et al., 2017 ). The results showed these pathways respond to floral induction of mango ( Prates et al, 2021 ).…”
Section: Discussionmentioning
confidence: 95%
“…Many studies have reported that drought can induce flowering in several plant species, including durian [10,11], mango [15], citrus fruits [9], longan [13], lime [12], loguat [14], and mangosteen [17]. A drought period lowers soil moisture and increases soil temperature.…”
Section: -3-soil Temperature and Moisture At Four Depth Levelsmentioning
confidence: 99%
“…Many studies have shown that mangosteen reproductive phenology (i.e., flowering and fruiting) is associated with climatic conditions (e.g., rainfall, temperature, radiation levels, and photoperiod), height above sea level, availability of shade, and geographical locations [2][3][4][5][6][7][8]. Drought-inducing flowering has been reported in several plant species, including citrus fruits [9], durian [10,11], lime [12], longan [13], loguat [14], mango [15], and mangosteen [5,16,17]. Many studies have reported that drought-inducing flowering in mangosteens with 15-30 dry days for flower bud formation and flowering, occurs naturally after the dry period [2,3,5,[17][18][19].…”
mentioning
confidence: 99%
“…The use of PBZ in excessive concentrations can lead to the accumulation of residues in the soil (Prates et al, 2021). The expectacy of this research is that the combination of PBZ treatment with drought stress can reduce residues in the soil to minimize environmental damage in support of environmental sustainability.…”
Section: Introductionmentioning
confidence: 97%